Community-Based Early Childhood Development Center as a Platform to Overcome Stunting in PAUD Kenanga Mekar Asri Semarang - Kustriyanti, Dwi; Boediarsih, Boediarsih; Hastuti, Witri; Rahayu, Hermeksi; Wulaningsih, Indah; Mardiyani; Sitepu, Andrew (Nuban Jaggadhita Center, 2024)
Purpose: This community-based early childhood development center program aims to promote early childhood growth and development by providing a safe stimulating environment and increased knowledge about nutrition that impacts improved dietary practices. Methodology: The method of activities carried out was chosen in the form of counseling, mentoring, and training. The approach uses participatory rural appraisal (PRA) and is modified with oriented project planning (OPP). These two approaches are to achieve a catfish pond/tilapia program as an innovation project and urban farming of various vegetables. This activity requires the participation and role of partners, with the principle of and for the community itself. Findings: The children were boys (60%) with the highest ages being 36 and 48 months (30%). The majority of children develop according to age (70%), of which 4 children (28.5%) are aged 30, 36 &; 48 months, 2 children (14.2%) are 42 months old, Suspect development is 30%, of which 2 children (33.3%) are 36 &48 months and 1 child (16.7%) is 42 and 30 months old. There is only 1 child (5%) who is underweight and male, none of whom are stunted.